(untitled) (Bangladesh Journal of Botany, 2026)
The study was carried out in three different environments with 25 (G1-G25) bread wheat genotypes. According to the stability biplot model, G7 was found to be moderately stable and high grain yielding, while G10 (Kate A-1) was determined to be the most sensitive genotype. In the genotype, genotype x environment (GGE) biplot graph, showing the ideal environment and genotype, principal component 1 (PC1) constituted 51.57% of the total variation and principal component 2 (PC2) constituted 31.05%. In terms of grain yield, the ideal environment was E2 and the ideal genotype was G7. The results indicated that environmental differences significantly affected selection criteria. E1 was identified as a suitable environment for selections focused on yield-related traits, particularly thousand-grain weight (TGW) and test weight (TW). In contrast, E3 was found to be more suitable for selections targeting quality traits, including zeleny sedimentation (ZS), protein ratio (PR), and wet gluten (WG). These findings indicate that E1 and E3 should be considered as suitable environments depending on the breeding objective. In the study, the fact that G10 was found far from the center of origin indicates that it contributes greatly to the variation and was also the genotype that adapts to specific environments. Bangladesh J. Bot. 55(1): 145-152, 2026 (March)